2015
DOI: 10.5539/res.v7n11p200
|View full text |Cite
|
Sign up to set email alerts
|

How Do Depression Medications Taken by Pilots Affect Passengers’ Willingness to Fly—A Mediation Analysis

Abstract: The mental health of airline pilots has been a concern for decades. In 2010, the United States Federal Aviation Administration began allowing four types of selective serotonin reuptake inhibitors (SSRIs) to be used by pilots suffering from depression. After a procedural wait period, pilots may be awarded a special issuance of their medical certificates to maintain flight currency. Missing from the literature was any research on consumer's perceptions of pilots taking antidepressants, along with some other appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This study also examines frequency of air travel in order to determine whether frequent travelers for business would indicate different willingness to fly than those who travel less or travel purely for pleasure. The Willingness to Fly scale ( Rice et al, 2015 , 2020 ) is a scale developed, and subsequently validated in numerous studies analyzing participant's desire to fly in various scenarios ( Rice and Winter 2015 ; Rice et al, 2015 ; Rice et al, 2015a , Rice et al, 2015b ; Winter et al, 2017 ). Therefore, the willingness to fly scale was selected as a valid measure of the outcome variable in the current study.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…This study also examines frequency of air travel in order to determine whether frequent travelers for business would indicate different willingness to fly than those who travel less or travel purely for pleasure. The Willingness to Fly scale ( Rice et al, 2015 , 2020 ) is a scale developed, and subsequently validated in numerous studies analyzing participant's desire to fly in various scenarios ( Rice and Winter 2015 ; Rice et al, 2015 ; Rice et al, 2015a , Rice et al, 2015b ; Winter et al, 2017 ). Therefore, the willingness to fly scale was selected as a valid measure of the outcome variable in the current study.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Several consumer research studies have showed that emotions play a key role when a person is put in a situation that involves decision-making, and can be a mediating effect in relation to consumer opinions and trust (Mehta, Rice, & Rao, 2016;Mehta, Rice, Winter, & Buza, 2017;Rice, Winter, Kraemer, Mehta, & Oyman, 2015;Winter, Rice, Friendenreich, Mehta, & Kaiser, 2017;Winter, Rice, & Mehta, 2014). As mentioned in the previous section, emotions can cloud a person's ability to make sensible decisions.…”
Section: Affectmentioning
confidence: 99%
“…While the purpose of this study is to gauge willingness to fly and whether that willingness is rooted in emotion, it follows previous studies inside and outside of aviation that have used affect as a potential mediator to explain the relationship between the condition and willingness (Babin, & Attaway, 2000; Baker & Cameron, 1996; Campbell, 2007; Rice, Winter, Kraemer, Mehta, & Oyman, 2015; Winter, Rice, & Mehta, 2014). This study anticipates finding similar results to the previous research that suggest that the relationship between condition and willingness will be mediated by affect or emotion.…”
Section: Federal Flight Deck Officer Program and Arming Pilotsmentioning
confidence: 99%